EXPERT-BASED ATTRIBUTE IDENTIFICATION AND VALIDATION ON FRACTION SUBTRACTION: A COGNITIVELY DIAGNOSTIC ASSESSMENT APPLICATION - Lokman Akbay; Ragip Terzi; Mehmet Kaplan; Katibe Gizem Karaaslan (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
In this study we describe the methodology used to identify and validate a set of expert-defined fraction subtraction related attributes. These attributes are expected to be mastered by 6th grade students toward proficiency. This research argues and demonstrates that state standards guiding subject instruction plays an important role in identification of the domain related fundamental attributes. This study also illustrates throughout implementation of cognitive diagnosis model framework, which is used to extract diagnostic information about students' specific strengths and weaknesses.DOI: http://dx.doi.org/10.22342/jme.9.1.4341.103-120